Assessing solid waste management strategy in higher education institutions of Indonesia: A case study of IPB University. Issue 1 (May 2021) - Rugatiri, J; Abidin, Z; Ismail, A
Abstract: Globally, the solid waste management sector is facing numerous challenges. To encourage solid waste management IPB University launched the Green Campus program 2020. The critical success of this program was fulfilled by awareness with the participation of the family of IPB University. The objective of this study was to assess the relationship between the awareness and respective practices' in solid waste management, among IPB University students. The study employed a descriptive research design with (n=108) randomly selected students. Data were analyzed and interpreted by using descriptive and inferential statistics. The study revealed that the students are highly aware of solid waste management, and also the students have good practices in terms of proper reducing and reusing, but moderately proper segregation, recycling, and disposal practices. The level of awareness of the students is influenced by their practices in waste segregation, reduction, reuse, and recycling but not influenced by their practices in terms of disposal. The study also revealed that the most waste generated in University dormitories was plastic bags, leftovers food, tissue papers, and cans waste. Meaningful recommendations were suggested to raise awareness among students in proper segregation and disposal practices.